Analyzing Drivers and Barriers of IMC in Healthcare: A Structural Approach Using M-TISM and Micmac - Golvin Peter, Ramesh Pai (Journal of Informatics Education and Research, 2024)
This study explores the structural relationships among the barriers and drivers influencing the adoption of Integrated Marketing Communications (IMC) using the Modified Total Interpretive Structural Modeling (M-TISM) technique. Through an extensive literature review and expert interviews, ten critical variables were identified, including regulatory constraints, budget limitations, lack of expertise, and technological challenges. The analysis involved creating a Structural Self-Interaction Matrix (SSIM), Reachability Matrix (RM), and Final Reachability Matrix (FRM) to examine the direct and indirect influences between these variables. The study applied MICMAC analysis to categorize these variables based on their driving and dependence power, revealing that high-driving-power variables like Budget Limitations (B2) and Regulatory Constraints (B1) are key drivers in overcoming barriers to IMC adoption, while variables like Internal Coordination Issues (B10) and Cultural Differences (B6) are more dependent. The study also utilized Level Partitioning and Conical Matrix methods to uncover the hierarchical relationships, providing a clear pathway for addressing the most influential barriers. The findings highlight the need for strategic focus on the most impactful drivers to enhance the adoption and effectiveness of IMC strategies. This research offers a valuable framework for practitioners and decision-makers in overcoming challenges and improving communication integration within organizations.